2017
DOI: 10.1002/ange.201708835
|View full text |Cite
|
Sign up to set email alerts
|

para‐Xylene Ultra‐selective Zeolite MFI Membranes Fabricated from Nanosheet Monolayers at the Air–Water Interface

Abstract: Supportinginformation and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 47 publications
2
47
0
Order By: Relevance
“…Prepared membranes exhibited moderate molecular sieving properties (separation factor of p ‐xylene from o ‐xylene was in the range 25–45), while p ‐xylene permeability (4 × 10 −7 mol m −2 s −1 Pa −1 at 150 °C) was improved in comparison with previous studies and it was comparable to that of the alumina used as a support for membrane preparation. Improved membranes were recently prepared using exfoliated MFI nanosheets using the floating‐particle coating method, which allowed for production of closely‐packed nanosheet monolayers . The density and uniformity of prepared films were higher in comparison with those obtained through Langmuir–Schaefer deposition and filtration methods.…”
Section: D Zeolitesmentioning
confidence: 99%
“…Prepared membranes exhibited moderate molecular sieving properties (separation factor of p ‐xylene from o ‐xylene was in the range 25–45), while p ‐xylene permeability (4 × 10 −7 mol m −2 s −1 Pa −1 at 150 °C) was improved in comparison with previous studies and it was comparable to that of the alumina used as a support for membrane preparation. Improved membranes were recently prepared using exfoliated MFI nanosheets using the floating‐particle coating method, which allowed for production of closely‐packed nanosheet monolayers . The density and uniformity of prepared films were higher in comparison with those obtained through Langmuir–Schaefer deposition and filtration methods.…”
Section: D Zeolitesmentioning
confidence: 99%
“…[3] Supported zeolite MFI membranes were recommended as ideal candidates for the separation of xylene isomers via vapor permeation or pervaporation owing to their high thermal and chemical stability as well as medium pore size. [4][5][6][7][8][9][10][11][12][13][14] Zeolite MFI membranes consist of two types of channels:s traight channels with circular pore size of 0.54 0.56 nm along the baxis and sinusoidal channels with elliptical openings of 0.51 0.55 nm along the a-axis.C onsidering the average pore size, zeolite MFI membranes are expected to selectively allow PX (with kinetic diameter of ca. 0.58 nm) to pass through, while excluding the larger OX and MX isomers (with kinetic diameter of ca.…”
mentioning
confidence: 99%
“…Indeed, previous studies have demonstrated that zeolite MFI membranes can be highly selective for PX over OX with separation factors from tens to hundreds (Table S1 in the Supporting Information), even up to ten thousand. [11] Notably,T sapatsis and co-workers reported the preparation of ah ighly b-oriented zeolite MFI membrane by asecondary growth method, [6] or by nanosheet monolayers, [11] which showed PX permeance of about 1.4 10 À7 mol/(m 2 sPa) and PX/OXs eparation factor up to about 10 000 via vapor permeation. However,the PX fluxes through the membrane are relative low,and the tests were performed with 1vol.…”
mentioning
confidence: 99%
“…[5,13] Fort he fabrication of oriented membranes with the MFI framework topology-which is globally used in large quantities in petroleum refining and chemical industries-oriented monolayers have been conventionally fabricated on porous substrates;that is, a-Al 2 O 3 or homemade SiO 2 substrates. [5,9,13,18] However,coating Al-free MFI (silicalite-1) crystals on porous substrates traditionally requires additional surface functionalization using organics,s uch as polymers,w hich serve to adhere the crystals to the substrate. [12,[19][20][21] While the recently developed filter coating and floating particle coating methods can yield closely packed monolayers of silicalite-1, these methods are limited to ultrathin nanosheets.…”
mentioning
confidence: 99%
“…[12,[19][20][21] While the recently developed filter coating and floating particle coating methods can yield closely packed monolayers of silicalite-1, these methods are limited to ultrathin nanosheets. [9,18] Furthermore, reports on the growth of highly b-oriented aluminosilicate MFI (ZSM-5) membranes with at unable Al content supported on porous substrates are scarce,e ven though this parameter is critical to control the wettability,s orption potential, cation exchange capacity,a nd concentration of Brønsted acid sites-all of which dictate performance. [7,[22][23][24][25] Herein, we use Na + as the mineralizer to eliminate intercrystallite defects and form homoepitaxially oriented, well-intergrown zeolite ZSM-5 membranes with at unable composition of Si/Al = 25-1 by secondary growth of asilicalite-1 monolayer that is rationally attached on ac ommercial porous ceramic substrate;that is,mesoporous g-Al 2 O 3 -coated a-Al 2 O 3 ,byelectrostatic adsorption without surface functionalization or organic coating.…”
mentioning
confidence: 99%